Digital Oral Histories for Reconciliation: The Nova Scotia Home for Colored Children History Education Initiative (DOHR) - Smith, Tony; Morrison, Gerald; Dorrington-Skinner, Tracy; Llewellyn, Kristina; Llewellyn, Jennifer; Roberts-Smith, Jennifer; Gibson, Lindsay; Peck, Carla (Journal of the Canadian Association for Curriculum Studies, 2020)
Digital Oral Histories for Reconciliation (DOHR) is a history education initiative to teach Grade 11 students about the Nova Scotia Home for Colored Children (NSHCC). The NSHCC, opened in 1921, was a segregated welfare institution for African Nova Scotian children. Residents suffered the effects of institutionalized racism in the Home throughout its 70 years. DOHR has partnered in the educational mandate of the restorative inquiry into the Home to co-design with the former residents a curriculum about their experiences (Province of Nova Scotia, 2015, p. 26). The purpose of the DOHR curriculum is for former residents to share their oral histories to develop students’ historical consciousness about institutionalized racism and to build right relations in their communities. The project was piloted in two Halifax area schools in October 2019. This symposium introduces attendees to the curriculum and shares initial findings from the pilot. Former residents share their impetus for the project, while other DOHR members share findings about the use of oral history—first person accounts of lived experiences with the past—as a restorative approach to redress of harms in education (e.g., Llewellyn & Llewellyn, 2015); how historical thinking lessons develop students’ historical consciousness—their sense-making of the past for orienting themselves to the present and future (Seixas 2004); and how DOHR’s use of virtual reality supports reconciliation with pedagogy-led (rather than technology-led) design principles (Kwon, 2019). To our knowledge, this is the first history education project centred on first-voice, to address reconciliation for African Nova Scotians.